Flipped Learning in Flipped Classrooms: A New Pathway to Prepare Future Special Educators. Issue 3 (3rd July 2019) - Brewer, Robin; Movahedazarhouligh, Sara
Abstract: Preparing high-quality special education teachers is the purpose of special education teacher education programs. Educators are focusing on ways to enhance traditional models of teaching and learning in higher education. One alternative, flipped learning, reverses a traditional model of learning by providing content typically presented during class lectures, outside of class through videos, online modules, and so on. During class, active learning occurs, applying concepts to hands-on activities. This qualitative study explored special education teacher candidates' perceptions regarding their experiences in a flipped course. To understand participants' experiences, teacher candidates participated in digitally recorded focus groups. Each transcribed recording was then analyzed using NVivo 11, and content analysis resulted in a variety of themes presented in this study with suggestions for practice and further research.